MEANS OF FORMING SUSTAINABLE MOTIVATION IN OF STUDENTS IN THE STUDY OF ENGLISH - O.V. Pakhomova (Academy of Cognitive and Natural Sciences, 2004)
The article reveals definite aspects in formation of steady student motivation while studying the English language, some terms and steps in its forming, the definite methods and criteria of its development and keeping on the constantly high level.